Parent and patient perceptions of medical marijuana in the childhood cancer context. Issue 4 (30th November 2020) - Ananth, Prasanna; Revette, Anna; Reed‐Weston, Anne; Das, Porag; Wolfe, Joanne
Abstract: Background: Medical marijuana (MM) is legal in 34 US jurisdictions. Yet, little is known about patient and parent perceptions of MM in pediatric cancer care. We examined attitudes, beliefs, and experiences regarding MM among parents of children with cancer and adolescent and young adult (AYA) patients, to help frame future research initiatives. Procedure: In this qualitative study, we conducted semi‐structured, one‐on‐one interviews with parents and AYAs at a comprehensive cancer center. Interviews were audio‐recorded, transcribed, and coded using both descriptive and inductive coding approaches. We used content and framework analysis to identify key themes. Results: Fifteen parents and 15 AYAs enrolled. Participants were generally receptive to MM use, concurrently weighing benefits and risks. Participants most often endorsed MM use for relief of nausea, anorexia, and pain. Simultaneously, participants identified concerns about MM, including potential physiologic and psychological effects on children and lack of research. However, concerns were frequently minimized, relative to chemotherapy or supportive care medications with perceived greater side effect profiles. Many participants expressed uncertainty regarding legal access, citing complex processes to obtain MM. Few participants had discussed MM with their oncologist, instead seeking guidance from the internet, family, or peers. Importantly, we elicited several misconceptions regarding MM, including its utility as cancer‐directed therapy. Conclusion: Patients and families are receptive to using MM, motivated by potential for symptom relief and cancer‐directed effects. Yet, lack of empiric evidence is a barrier, underscoring the need for robust clinical trial data to support MM recommendations and use.